Additive Manufacturing: A Game Changer in Supply Chain Design - Victor Verboeket; Harold Krikke (Logistics, 2019)
Additive Manufacturing (AM) is a digital manufacturing technology that enables companies to rethink their supply chain (SC) design. By means of literature synthesis, we build new knowledge about the mechanisms AM induces to improve SC design and performance, as well as the disruptive changes AM can cause. We investigate opportunities to optimize SC design for manufacturing purposes by exploiting the characteristics of AM, e.g., its freedom in terms of shape design and complexity and the absence of a need for object-specific tools. We study the roles of demand, assortment, IT systems, sourcing, manufacturing, knowledge, warehousing, and transportation, and explore the effects and tradeoffs on various SC performance outcomes, including cost, assets, and responsiveness. The contribution of this article is twofold. First, through literature synthesis, we construct six AM SC mechanisms that can be used in SC design to achieve desired SC outcomes for AM production applications in certain (business) contexts. Second, we identify the disruptive ‘game-changing’ effects of AM for SC stakeholders. This knowledge can be used by other researchers to develop further research. Moreover, general and logistics managers can use the results to fully exploit the potential of AM for designing much improved supply chains. Innovators and policy makers can use the results to understand the potential game-changing consequences of AM.